1984
DOI: 10.1093/oxfordjournals.jbchem.a134952
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin S: A Cysteine Proteinase Inhibitor of Human Saliva

Abstract: An acidic protein of human saliva, which we named SAP-1 previously, is now shown to be an inhibitor of several cysteine proteinases. The protein inhibited papain and ficin strongly, and stem bromelain and bovine cathepsin C partially. However, it did not inhibit either porcine cathepsin B or clostripain. The mode of the inhibition of papain was found to be non-competitive. The name cystatin S has been proposed for this salivary protein in view of the similarities in activity and structure to other cysteine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 0 publications
2
60
0
1
Order By: Relevance
“…(30). It has been suggested that the active site of the cysteine proteinase inhibitors may be located between positions 53 and 69 because this segment is the most conserved region in all known cystatins (19,33,(35)(36)(37). Moreover, human kininogens, which inhibit papain and cathepsin L (38), have a duplicated segment homologous to positions 53-69 and are codified by discontinuous DNA segments (39) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(30). It has been suggested that the active site of the cysteine proteinase inhibitors may be located between positions 53 and 69 because this segment is the most conserved region in all known cystatins (19,33,(35)(36)(37). Moreover, human kininogens, which inhibit papain and cathepsin L (38), have a duplicated segment homologous to positions 53-69 and are codified by discontinuous DNA segments (39) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only recently has the role of mammalian kininogens in the inhibition of cysteine proteinases been clearly established [27]; ra kin, rat kininogen (major acutephase protein) [30]; bo col CPI, bovine colostrum cysteine proteinasc inhibitor [31]; ch cys, chicken cystatin from egg white [32, 331; hu cys, human cystatin (y-trace) from plasma [34, 351; hu SAP, human salivary acidic protein [36]; hu ste, human stefin from granulocytes [37]; hu liv CPI, human liver cystatin B [38]; ra epi TPI, rat epidermal thiol proteinase inhibitor [39]; ra liv TPI, rat liver thiol proteinase inhibitor inhibitors revealed that two potential reactive sites represented by the pentapeptide Gln-Val-Val-Ala-Gly might be present in the human kininogen heavy chain. An extended region of 27 amino acids centered around the putative reactive sitc shows extensive sequence homologies between the heavy chains of human, rat and bovine kininogens (Fig.…”
Section: Homologq Between Human High-m Kininogen Und Mummuliun Cystmentioning
confidence: 99%
“…HRGD2 was most homologous (22% identical) to human cystatin S [8] as well as other cystatins and HKHDS. The similarity of Fig.…”
mentioning
confidence: 99%